2021
DOI: 10.1016/j.jiph.2021.08.030
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related treatment and outcomes among COVID-19 ICU patients: A retrospective cohort study

Abstract: Background The COVID-19 pandemic remains an immediate and present concern, yet as of now there is still no approved therapeutic available for the treatment of COVID-19.This study aimed to investigate and report evidence concerning demographic characteristics and currently-used medications that contribute to the ultimate outcomes of COVID-19 ICU patients. Methods A retrospective cohort study was conducted among all COVID-19 patients in the Intensive Care Unit (ICU) of As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
3
6
4
Order By: Relevance
“…Although male patients represented a higher proportion of the nonsurvival groups, there was no significant difference in terms of gender. However, this observation was consistent with many studies [ 31 , 32 , 37 , 38 ]. Among studies that assessed the mortality of COVID-19 patients on tocilizumab in Saudi Arabia, our study reported an overall mortality of 21%.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although male patients represented a higher proportion of the nonsurvival groups, there was no significant difference in terms of gender. However, this observation was consistent with many studies [ 31 , 32 , 37 , 38 ]. Among studies that assessed the mortality of COVID-19 patients on tocilizumab in Saudi Arabia, our study reported an overall mortality of 21%.…”
Section: Discussionsupporting
confidence: 93%
“…In comparison, other studies reported 16.1% (n = 62) 28-day mortality [36]. In terms of mortality among ICU patients, the current study reported 38.5%, while other studies reported 31.1% (n = 61) [37] and 18.9% (n = 37) [38] mortality. However, worldwide, there is inconsistency in the percent of mortality of COVID 19 patients on tocilizumab, which in some studies has been reported to be as low as 13.4% (Asian-Indian) and up to 43.2% (American) [31,32,37,38].…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The involvement of CRS in COVID-19 worsening is demonstrated by the increased proinflammatory factors that are seen in severe COVID-19 patients [ 9 ]. Studies report varying success rates of TCZ in patients with COVID-19 [ 10 14 ]. Predictors of poor outcome in COVID-19 patients receiving TCZ, according to studies conducted globally, include older age, comorbidities such as hypertension, diabetes mellitus, and immunosuppression, days from diagnosis until TCZ administration, elevated C-reactive protein (CRP), lactate dehydrogenase (LDH), troponin I, and neutrophil levels [ 15 – 17 ].…”
Section: Introductionmentioning
confidence: 99%